Strategy and Dynamics of the Curriculum of the Islamic Boarding School of Darul Muhajirin Lumajang : Strategy, Dynamics, KMI (Mu’allimin Al-Islamiyah Curriculum) - Muhlason; Wahyuni, Hana Catur (Indonesian Journal of Innovation Studies, 2026)
General Background: The Kulliyatul Mu’allimin Al-Islamiyah (KMI) curriculum integrates formal and informal education within a 24-hour pesantren system. Specific Background: At Darul Muhajirin Islamic Boarding School, KMI implementation involves human resources, student management, leadership, discipline, and infrastructure. Knowledge Gap: Its implementation still faces limited qualified teaching staff, inadequate facilities, and restricted clean-water availability. Aims: This study examines KMI implementation, supporting programs, and its strengths and weaknesses at Darul Muhajirin Lumajang. Results: The findings show that KMI is supported by professional management, kiai leadership, student organization, regular supervision, teacher development, and entrepreneurship education, while limitations remain in human resources and infrastructure. Novelty: The study identifies collaboration with higher education and community-based entrepreneurship through Damhar Mart as distinctive strategies. Implications: KMI implementation requires teacher capacity development, professional management, student discipline, and community-supported infrastructure. Key Findings Highlights Kiai leadership supports teacher development and institutional management. Student organization reinforces discipline across pesantren activities. Community collaboration supports entrepreneurship and infrastructure provision. Keywords: KMI Curriculum, Islamic Boarding School, Curriculum Implementation, Human Resources, Pesantren Management